The epidemiology of emergency presentations for falls from height across Western Victoria, Australia. (June 2020) - Holloway-Kew, Kara L.; Baker, Tim R.; Sajjad, Muhammad A.; Kotowicz, Mark A.; Livingston, Patricia M.; Khasraw, Mustafa; Hakkennes, Sharon; Dunning, Trisha L.; Brumby, Susan; Page, Richard S.; Sutherland, Alasdair G.; Brennan-Olsen, Sharon L.; et al.
Abstract: Background: In order to implement intervention strategies to prevent falls from height, epidemiological data are needed. The aim of this study was to map emergency presentations for falls from height in residents aged ≥40 yr of the western region of Victoria, Australia. Methods: Emergency presentations following a fall from height (≥1 m) were obtained from electronic medical records for 2014–2016 inclusive. For each Local Government Area, age-standardised incidence rates (per 10, 000 population/year) were calculated. Results: The age-standardised incidence rate was lowest in the Northern Grampians (3.4 95%CI 0.8–5.9), which has several main industries including health care, agriculture and manufacturing. The highest rates occurred in Corangamite (26.0 95%CI 19.9–32.0), Colac-Otway (23.7 95%CI 18.5–28.8) and Moyne (22.5 95%CI 16.8–28.3), which are sparsely populated (15, 000–20, 000 people each). Patterns were similar for men and women. Most falls occurred during "leisure" (38.0%), followed by "other work" (15.4%). Men were more likely than women to experience a fall from height while undertaking work activities. Many falls occurred in the home (53.2%). Conclusion: Future research should inform strategies to prevent falls from height in the region. This could include specific locations such as the home or farm, and during leisure activities or work.